Nanozyme-Engineered Hydrogels for Anti-Inflammation and Skin Regeneration - Kurian, Amal George; Singh, Rajendra K.; Sagar, Varsha; Lee, Jung‑Hwan; Kim, Hae‑Won (Nano-Micro Letters, 2024)
Inflammatory skin disorders can cause chronic scarring and functional impairments, posing a significant burden on patients and the healthcare system. Conventional therapies, such as corticosteroids and nonsteroidal anti-inflammatory drugs, are limited in efficacy and associated with adverse effects. Recently, nanozyme (NZ)-based hydrogels have shown great promise in addressing these challenges. NZ-based hydrogels possess unique therapeutic abilities by combining the therapeutic benefits of redox nanomaterials with enzymatic activity and the water-retaining capacity of hydrogels. The multifaceted therapeutic effects of these hydrogels include scavenging reactive oxygen species and other inflammatory mediators modulating immune responses toward a pro-regenerative environment and enhancing regenerative potential by triggering cell migration and differentiation. This review highlights the current state of the art in NZ-engineered hydrogels (NZ@hydrogels) for anti-inflammatory and skin regeneration applications. It also discusses the underlying chemo-mechano-biological mechanisms behind their effectiveness. Additionally, the challenges and future directions in this ground, particularly their clinical translation, are addressed. The insights provided in this review can aid in the design and engineering of novel NZ-based hydrogels, offering new possibilities for targeted and personalized skin-care therapies. Highlights: 1 Nanozyme-based approaches to produce therapeutic hydrogels. 2 Enzymatic mechanisms and multifunctional roles of nanozyme-engineered hydrogels for skin therapy. 3 Therapeutic actions of nanozyme-engineered hydrogels in inflamed skin tissues. 4 Mechanical and immunological aspects of skin therapy guided by nanozyme-engineered hydrogels. 5 Promising directions and challenges of nanozyme-inspired hydrogel platforms.